Challenges in Crowdsourcing Geospatial Data to Replace or Enhance Official Sources - Clodoveu A. Davis (Disegnare con)
Urban dwellers demand geospatial data on various aspects of contemporary life. Governmental sources account for several important data categories, but not necessarily up-to-date, or even covering all aspects. Technologies such as smartphones allow citizens to become geospatial data producers and to contribute with valuable georeferenced data in near real time. Crowdsourced often has problems in aspects such as coverage, reliability and positional accuracy. This paper focuses on challenges that exist in the integration of geospatial data provided by governmental or corporate sources to crowdsourced data, provided dynamically and voluntarily by concerned citizens, or unconsciously through online tools and social networks. DOI: https://doi.org/10.20365/disegnarecon.20.2018.1